Meningkatkan Loyalitas Merek Dengan Pengalaman Merek Melalui Cinta Merek dan Kepercayaan Merek - Lailatul Qomariyah; Didit Haryadi (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose- The purpose of this study was to examine and analyze the effect of brand experience on brand loyalty through brand love and brand trust The study uses a descriptive quantitative method with a causal approach.Methodology - The research method uses a descriptive quantitative method with a causal approach with a sample of 162 respondents. Questionnaire answers were measured using a scale interval of 1 10. Data were analyzed using the SmartPLS version 3.29 software.Findings - Results of this study stated that brand experience has a positive and significant effect on brand loyalty, brand experience has a positive and significant effect on brand love, brand experience has a positive and significant effect on brand trust, brand love has a positive and significant effect on brand loyalty, brand trust has a positive and significant effect on brand loyalty.Originality/Novelty - Brand love and brand trust can mediate the effect of brand experience in partial mediation on brand loyalty.Implications - Able to build brand loyalty, namely by increasing brand experience, brand love, and brand trust. To increase brand love is to improve brand experience. Increase brand trust, namely by increasing the experience on the brand. Building brand loyalty by enhancing the brand experience can be through brand love and brand trust.